Plastic Surgery Away Rotations During the Coronavirus Disease Pandemic: A Virtual Experience. Issue 6 (1st June 2022) - Tucker, A. Blake; Pakvasa, Mikhail; Shakir, Afaaf; Chang, David W.; Reid, Russell R.; Silva, Amanda K.
Abstract : Background: Plastic surgery has traditionally been a specialty that places a strong emphasis on away rotations during the final year of medical school. These rotations allow the program and residency candidates to become better acquainted and are often crucial, as a large portion of applicants match at programs where they rotated. The coronavirus disease 2019 (COVID-19) pandemic forced many institutions to modify their educational curriculums when away rotations were canceled. We present our experience creating and implementing a virtual plastic surgery rotation. Methods: Our virtual program was designed to mirror the in-person away rotations as much as possible. Prerotation and postrotation surveys from the students as well as feedback interviews with the students, residents, and faculty were used to gather information on the experience. Results: We created a 2-week curriculum including approximately 20 hours of lecture time, 28 hours of operating room time, 2.5 hours of one-on-one mentorship, and 3 hours of social opportunities. Students reported that they learned more about plastic surgery and the residency program, but in contrast to this, some found it difficult to make an impression. Conclusions: We developed a novel 2-week virtual curriculum that provided visiting medical students from across the country an opportunity to learn more about plastic surgery and our residency program. Virtual learning is becoming a vital part of education, and our study provides pearls and pitfalls when structuring these experiences.